Underpinning implications of instructional strategies on assistive technology for learning disability: a meta-synthesis review. - Thapliyal, Monika; Ahuja, Neelu Jyothi (Disability & Rehabilitation: Assistive Technology, 2023)
This article reviews the instructional strategies used by assistive technologies and maps their problem manifestation and effectiveness for children with learning disabilities. The objective of this article is to investigate the most common types of assistive tools used in learning to study their attributes, limited to the needs of learners with the condition of dyslexia, dysgraphia and dyscalculia. It studies currently available low, mid and high-level assistive learning technologies available to deal with problems faced by these learners. Assistive tools studied in this article range from simple hardware tools to multi-sensory software. A simple analytical framework by interlinking, Problem Manifestation, Underpinned Implication, Instructional Strategy and Cognitive Strength Developed (PISC) is formulated to examine the tools. Five assistive tools types (non-electronic products, low-tech products, mid-tech products, high-tech products apps and learning software) for each learning disability are identified, analysed and associated learning implication is studied under PISC framework. This helps to map the problems and learning style of learning disabled and analyses the underpinned implication along with the corresponding development of skills (cognitive, affective or psychomotor) by these assistive technologies. Performance of identified assistive tool types using PISC framework is analysed. Findings are reported and discussed. Available assistive tools are not learning disability specific. So, in order to differentiate the learning path of a Learning Disabled learner from that of a Non-Learning Disabled learner, study is conducted under four attributes of PISC framework: Problem Manifestation, Underpinned Implication, Instructional Strategy and Cognitive Strength. Available assistive tools in the field of remedial education are found to be problem centric and only able in dealing with single academic learning need of a learner with specific learning difficulty. The mapping of the available assistive technologies under PISC framework provides a detailed structure for the selection of most suited assistive tool as per learning requirement of a learner with learning disability. This study also conclude the non- availability of the High-tech assistive tools and Educational Software specifically designed for learners with learning disability.